Suspicion of heparin-induced thrombocytopenia in internal medicine: How appropriate is the ordering of anti-PF4/heparin antibody testing?. (3rd October 2015) - Beauverd, Yan; Boehlen, Françoise; Tessitore, Elena; Gerstel, Eric; Fontana, Pierre; Nendaz, Mathieu; Perrier, Arnaud; Reny, Jean-Luc
Abstract: Thrombocytopenia is frequent in hospitalized patients, and heparin-induced thrombocytopenia (HIT) is often suspected when a decrease in platelet count is concomitant with heparin treatment. ELISA tests used for anti-PF4/heparin antibodies detection usually have high sensitivity but only fair specificity for HIT. Pre-test probability scores (such as 4Ts or HEP scores) have been validated and a low probability score rules out HIT without anti-PF4/heparin testing. The aims of this study are to evaluate the appropriateness of anti-PF4/heparin testing according to pre-test probabilities of HIT and to compare the abilities of the 4Ts and HEP scores to avoid inappropriate anti-PF4/heparin testing. This retrospective observational study included 74 consecutive patients hospitalized in a general internal medicine division who had anti-PF4/heparin testing for suspicion of HIT. 4Ts and HEP scores were computed retrospectively. About 73% of patients who had ordering of an anti-PF4/heparin were at low risk according to the 4Ts score, and 46% according to the HEP score. Heparin was discontinued in 61% and 62% of low-risk patients according to 4Ts and HEP scores and switched to alternative anticoagulant in 31% and 32% of them, respectively. No case of HIT was diagnosed in patients with a low-risk score. One major bleeding and no thrombosis were observed. For the 4Ts score, the sensitivity was 100%, the negative predictive value (NPV) was 100%, the specificity was 77%, and the positive predictive value (PPV) was 20% (95% CI: 7–44). For the HEP score, the sensitivity was 100%, the NPV was 100%, the specificity was 49%, and the PPV was 10%. In conclusion, pre-test probability scores were vastly underused in this internal medicine population despite their ability to rule out HIT without laboratory testing in a large proportion of patients. Appropriate use of those instruments should be actively promoted.